Künstliche Intelligenz und menschliche Gesellschaft - Kovács, László (De Gruyter, 2023)
Artificial intelligence exceeds the capabilities of humans in many ways. Now, if AI surpasses the achievements of human intelligence, where and why will humans remain irreplaceable in how we will live, shape our society, and work in the future? Speakers from basic and applied research, business, and society will contribute to the answers from their respective perspectives.